Snacking Habits and Difficulty Eating (Picky Eater) Incidence in Preschool Children in East Java - Tika, Zummatul Atika; Setianingsih, Yana Agus; Larasati, Lintang Ayu; Indriyani, Eny; Kunaryanti, Kunaryanti (YCMM, 2024)
Picky eating is a significant challenge among preschool children, characterized by their reluctance or selectiveness towards certain foods. This behavior not only troubles parents but also raises concerns about meeting children's crucial nutritional needs during their growth period. In East Java, a study aimed to explore the correlation between snacking habits and the prevalence of picky eating in preschoolers. Conducted through a descriptive analytic approach with a cross-sectional design, the research involved 400 respondents sampled through accidental selection. Findings revealed that a majority of preschoolers in the region had a habit of snacking more than twice a day (59.2%), while a considerable proportion (54.0%) experienced difficulty with eating. Statistical analysis further indicated a significant association (p < 0.05) between snacking habits and the incidence of picky eating. This underscores the importance of understanding and managing children's snacking behaviors to address picky eating tendencies and ensure adequate nutrition during this critical developmental stage.